Understanding of micro-alloying on plasticity in Cu46Zr47−xAl7Dyx (0≤ x ≤ 8) bulk metallic glasses under compression: Based on mechanical relaxations and theoretical analysis. (July 2016) - Qiao, J.C.; Yao, Y.; Pelletier, J.M.; Keer, L.M.
Abstract: Lacking of plasticity at ambient temperature severely hinders the wide applications of bulk metallic glasses, and a significant challenge is to improve the plasticity. Based on the metallurgical physics, micro-alloying can be applied to adjust metallic glasses plasticity. In the current work, dynamic mechanical relaxation of Cu46 Zr47−x Al7 Dyx (0 ≤ x ≤ 8) bulk metallic glasses has been investigated experimentally by dynamic mechanical analysis. Compressive tests have been performed to investigate mechanical properties of the Cu-based bulk metallic glasses at both ambient as well as cryogenic temperatures. The results indicated that by modifying the chemical composition, plastic deformation and dynamic mechanical relaxation processes are changed. The influence of Dysprosium (Dy) on plastic deformation is possibly related to the Johari-Goldstein (JG) relaxation in the metallic glasses. A kinetic model which may be predict the mechanical relaxation behavior and atomic mobility of the metallic glasses. In addition, experimental analyses show that thermal properties can be affected by the Dy addition of the Cu-based bulk metallic glasses. Our investigations demonstrated that micro-alloying of Dy could play an important role to influence the Cu46 Zr47−x Al7 Dyx bulk metallic glasses plasticity. In order to explain this behavior, the quasi-point defects theory was used to describe the microstructural heterogeneity. We postulate that the compressive plasticity is directly associated with local heterogeneity and relaxation modes for metallic glasses. Graphical abstract: Highlights: Compressive plasticity of Cu-based BMGs strongly depends on the dysprosium addition. JG relaxation is less evident with increasing Dy content for the Cu-based BMGs. Effect of dysprosium on plastic deformation is possibly linked to JG relaxation. Compressive plasticity is associated with local heterogeneity based on the QPD model.